BPJS (BADAN PENYELENGGARA JAMINAN SOSIAL) DITINJAU DARI HUKUM ISLAM - Zulhendra, Joni (Normative Jurnal Ilmiah Hukum, 2022)
Health is a basic right of every person, and all citizens are entitled to health services. Taking into account the level of health urgency including carrying out the mandate of the 1945 Constitution, the government at both the central and regional levels has made several efforts to improve the ease of access to health facilities. 1. The perspective of Islamic law on the Social Security Administering Body (BPJS) Health in Indonesia which has the principle of social insurance according to the author is that the current conditions are not right because it can cause harm, namely the monthly contributions/premiums that will be deposited to the BPJS are still too high and the existence of the determination of sanctions for those who do not pay dues, the BPJS health program still contains elements of injustice in the concept of At Takaful Al Ijtma', with the contributions given there is a separation of the poor, middle and rich, especially in service, BPJS health in practice still contains elements of maishir, gharar, and usury, so according to the author the law falls into syubahat.